THE CLINICAL MANIFESTATIONS OF CALCIUM PYROPHOSPHATE CRYSTAL DEPOSITION DISEASE - F. M. Kudaeva; S. A. Vladimirov; M. S. Eliseev; A. V. Volkov; M. V. Severinova; V. G. Barskova (Научно-практическая ревматология, 2014)
Objective: to provide the clinical characteristics of joint injury in patients with calcium pyrophosphate crystal (CPC) deposition disease.Subjects and methods. The trial enrolled 68 patients (43 women, 25 men) with a verified diagnosis of CPC deposition disease. Their mean age was 60.2±11.8 years and disease duration was 7.5±6.4 years. Examination revealed the presence of arthritis and arthralgias. Polarizing microscopy with an Olympus CX31-P compensator was used to detectcrystals in synovial fluid. X-ray study of the knee joints was performed in the anteroposterior and lateral projections and that of the hand joints was in the frontal projection, Ultrasonography (USG) of the knee and wrist joints was done using a GE Voluson-I transducer.Results. A concurrence of arthritis and arthralgias was noted in 37 (54%) patients; 24 (36%) patients had arthralgias only; 7 (10%) had arthritis only. Arthritis affecting the knee, wrist, ankle, and first metacarpophalangeal joints was observed in 53, 15, 12, and 6% of cases, respectively. There was acute arthritis in 18% of the patients and chronic arthritis in 39%; the rate of CPC osteoarthrosis was 43%. Joint USG diagnosed knee and wrist joint chondrocalcinosis in 94 and 56% of the patients, respectively. USG could reveal asymptomatic wrist joint chondrocalcinosis significantly more often (in 56 and 17% of the patients, respectively; p = 0.008). Besides, USG could visualize synovitis in the knee joints in 88% of the patients with isolated arthralgias in them and synovitis in the wrinkle joints in 52% of the patients without clinical signs of inflammation in them.Conclusion. Osteoarthrosis is the most common form of CPC deposition disease. Knee joints in this disease are most frequently involved. Joint USG is of more informative value in detecting chondrocalcinosis than X-ray study; USG can also identify synovitis in the intact joints.